RASIONALITAS PENGAMBILAN KEPUTUSAN KB SUNTIK SEBAGAI ALAT KONTRASEPSI WANITA USIA SUBUR DI KABUPATEN TULUNGAGUNG - Nurchahyati, Erika Vivian (Paradigma, 2022)
High fertility causes an increase in population. To prevent it, the government increases socialization about family planning programs, including the people of Tulungagung Regency. It aims to increase the use of contraceptives to prevent pregnancy. However, in its application there is still a gender gap. This can be seen from the number of contraceptives for women compared to men. Because this causes the assumption that women must use contraception. So that it makes women of childbearing age tend to use contraceptives that are widely used by the community, namely injectable contraception. Although there are some side effects of injectable contraceptives, such as changes in physical shape which in some women cause insecurity. The purpose of this study was to determine the rationality of decision making in injectable family planning as a contraceptive for women of childbearing age in Tulungagung Regency. This study uses a qualitative research method and The theory used is Max Weber’s concept of rationality for analyzing data. The research subjects used purposive and women of childbearing age in Mergayu Village as the research subjects. The results show that there are four rationalities that influence decision making. Instrumental rationality is that there is no desire to have more children, the desire to regulate the birth period of children and save costs and time. Value rationality due to religious values, children’s values and socio-cultural values. Affective rationality is due to the feeling of giving in to husband, husband’s support and no fear of using injectable family planning. The traditional rationale is that parents who have used injectable contraception also join their neighbors and friends who use injectable contraception. Keywords :Rationality, Decision Making, injectable family planning, Women of childbearing age, contraception